1997
DOI: 10.1007/pl00009701
|View full text |Cite
|
Sign up to set email alerts
|

Stem xylem features in three Quercus (Fagaceae) species along a climatic gradient in NE Spain

Abstract: AbstractmStem xylem features in two evergreen Quercus species (Q. coccifera and Q. ilex) and a deciduous one (Q. faginea) were analysed along an Atlantic-Mediterranean climatic gradient in which rainfall and winter cold experience strong variation. Mean maximum vessel diameter, vessel density, vessel element length, xylem transverse sectional area, Huber value (xylem transverse sectional area per leaf area unit), theoretical leaf specific conductivity (estimated hydraulic conductance per leaf area unit) and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
97
2
10

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(117 citation statements)
references
References 35 publications
(33 reference statements)
6
97
2
10
Order By: Relevance
“…In this study, the overall frequency distribution of vessel was left-skewed, as previously reported for Q. faginea (Villar-Salvador et al 1997, Corcuera et al 2004a, Alla & Camarero 2012, Q. robur and Q. ilex (García-González & Eckstein 2003, Campelo et al 2010, Corcuera et al 2004b). The vessel distribution seems age-related, and the …”
Section: Discussionsupporting
confidence: 78%
“…In this study, the overall frequency distribution of vessel was left-skewed, as previously reported for Q. faginea (Villar-Salvador et al 1997, Corcuera et al 2004a, Alla & Camarero 2012, Q. robur and Q. ilex (García-González & Eckstein 2003, Campelo et al 2010, Corcuera et al 2004b). The vessel distribution seems age-related, and the …”
Section: Discussionsupporting
confidence: 78%
“…In the chaparral flora of California, the flora of South Western Australia and in a comparison between a Mexican wet rain forest and a dry forest, species occurring in moister sites generally had the larger xylem vessel diameters and longer vessels [2,4,5]. The same trend was found within some species from the genus Quercus along a climatic gradient in NE Spain [24]. Nevertheless, xylem resistance of roots and shoots may account for only 20 -30% of the total plant hydraulic resistance.…”
Section: Discussionmentioning
confidence: 60%
“…Hydraulic architecture at tree level reflects the environmental conditions e.g. water availability and air temperature (Villa-Salvador et al 1997;Noshiro and Baas 1998;Schreiber et al 2012). Crown architecture growth is also reflected in hydraulic architecture as the xylem anatomy varies according to e.g.…”
Section: Hydraulic Tree Architecturementioning
confidence: 99%